Contribution to the molecular characterization of osteoarthritis and osteoporosis phenotypes associated with hereditary hemochromatosis - F. Simao, Marcio (2019)
In this study, we aimed to investigate the molecular mechanisms responsible for development of osteoarthritis (OA) and osteoporosis (OP) phenotypes in hereditary hemochromatosis using the Hfe-KO mouse model. Results from the analysis of Hfe-KO mice articular cartilage showed that Hfe loss of function alone is not enough to promote an OA-like phenotype and there were no evidences for high iron deposition in articulations of Hfe-KO mice. However, in vitro characterization of Hfe-KO primary chondrocytes exposed to 50μM of iron citrate produced an OA-like phenotype, with lower extracellular matrix production and increase metalloproteases expression. In addition, we identified the presence of iron metabolism dysregulation in Hfe-KO cells which showed an increase in intracellular iron levels relatively to wild type (WT). These results suggested that OA phenotype results from the conjugation of Hfe-KO with direct iron overload exposure and / or other synergistic variables. In contrast, Hfe-KO mice (12- months-old) showed a bone loss phenotype with significant decrease in trabecular and subchondral bone. At 6 months of age no differences were observed in WT and Hfe-KO mice bone kept under standard diet but when subject to iron rich diets they showed opposite bone phenotypes, with increased bone mineralization for WT, likely resulting from a decrease in osteoclast activity, and bone loss for Hfe-KO mice associated with iron toxicity in bone tissue. In conclusion, our results indicate that iron rich diet promotes bone loss phenotype in Hfe-KO mouse model while it is not sufficient to induce OA in the absence of other insults.